Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1016/0301-0082(94)00063-n
|View full text |Cite
|
Sign up to set email alerts
|

'Vestibular compensation: neural plasticity and its relations to functional recovery after labyrinthine lesions in frogs and other vertebrates

Abstract: Removal of the labyrinthine organs on one side is followed by a number of severe postural and dynamic reflex deficits. Some of these deficits, in particular the posture of head and body, are normalized again over a period that varies strongly between species. Other, more persistent motor deficits are substituted, e.g. by the saccadic system. This partial normalization of the function is accompanied by changes in response properties of the central vestibular neurons on the operated side. Available evidence sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
2
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(155 citation statements)
references
References 0 publications
6
141
2
1
Order By: Relevance
“…This function could be more independent of the vestibular cues [16]. The data also point to the permanent role of vision in compensating the vestibularly induced deficits (see references [12,29,39] for reviews), including the spatial orientation impairments. The lateral deviation towards the lesioned side in patients tested EC after UVN was higher for the normal locomotion speed.…”
Section: Changes In Locomotor Trajectory Deviationmentioning
confidence: 78%
“…This function could be more independent of the vestibular cues [16]. The data also point to the permanent role of vision in compensating the vestibularly induced deficits (see references [12,29,39] for reviews), including the spatial orientation impairments. The lateral deviation towards the lesioned side in patients tested EC after UVN was higher for the normal locomotion speed.…”
Section: Changes In Locomotor Trajectory Deviationmentioning
confidence: 78%
“…Changes in the shape of synaptic potentials have been reported in the vestibular compensation process of frogs (Dieringer andPrecht 1977, 1979a,b;Galiana et al 1984), although the physiological mechanism underlying those changes remains unknown. In the present study, we found that the peak amplitude of excitatory and inhibitory PSPs as well as their rise rate and half decay time showed complex changes depending on the polarity and laterality (Fig.…”
Section: Peak Amplitude Rise Rate and Half Decay Time Of Pspsmentioning
confidence: 99%
“…However, this posture is gradually normalized to restore the original symmetrical posture. The posture compensation following partial destruction of the geotactic sense organ has been well known in many animals including vertebrates (Smith and Curthoys 1989;Darlington and Smith 2000;Dieringer 1995) and invertebrates (Schöne 1954(Schöne , 1971Sakuraba and Takahata 1999), the time required for the recovery depending on the animal species, ranging from several hours (rat) to weeks (rabbit). The neuronal mechanisms underlying the behavioral recovery, however, largely remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…As regards more specific studies on the effects of vestibular neurectomy in the frog, since the early 1970s Dieringer has studied the vestibular nucleus, spinal cord, and cerebellum. Dieringer (1995) reported the sole finding on the response of Purkinje neurons to stimulation of the eighth nerve; however, no mention was made of the Purkinje cells of the corpus cerebelli or vestibulocerebellum.…”
Section: Nos Induction After Axotomymentioning
confidence: 99%
“…In the extensive literature on vestibular compensation (for review, see Dieringer, 1995), the frog has also been considered as a neurobiological model. The involvement of Purkinje cells following the stimulation of the eighth nerve has also been reported (Dieringer and Precht, 1979a, b).…”
mentioning
confidence: 99%